2015
DOI: 10.1517/17425255.2015.1048222
|View full text |Cite
|
Sign up to set email alerts
|

Detecting reactive drug metabolites for reducing the potential for drug toxicity

Abstract: Information derived from state-of-art mechanistic drug metabolism studies can be used successfully to direct medicinal chemistry towards the synthesis of candidate drugs devoid of bioactivation liabilities, while maintaining desired pharmacology and pharmacokinetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 107 publications
0
19
0
Order By: Relevance
“…Most importantly, ribociclib was ready to undergo metabolic activation to form highly reactive intermediate 1,4‐benzenediamine. Reactive metabolites can covalently bind to protein, DNA, RNA and other macromolecules and, therefore, the toxicity (Brink, Pähler, Funk, Schuler, & Schadt, ; Grillo, ; Tang & Lu, ). This metabolic pathway is responsible for the toxicity of ribociclib.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, ribociclib was ready to undergo metabolic activation to form highly reactive intermediate 1,4‐benzenediamine. Reactive metabolites can covalently bind to protein, DNA, RNA and other macromolecules and, therefore, the toxicity (Brink, Pähler, Funk, Schuler, & Schadt, ; Grillo, ; Tang & Lu, ). This metabolic pathway is responsible for the toxicity of ribociclib.…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, ribociclib was ready to undergo metabolic activation to form highly reactive intermediate 1,4-benzenediamine. Reactive metabolites can covalently bind to F I G U R E 3 Extracted ion chromatogram of ribociclib-glutathione (GSH) adducts (a) in human liver microsomes and their MS 2 spectrum (b) and the proposed fragmentation pathways (c) F I G U R E 4 Proposed mechanism of the formation of GSH adducts in human liver microsomes in the presence of GSH protein, DNA, RNA and other macromolecules and, therefore, the toxicity (Brink, Pähler, Funk, Schuler, & Schadt, 2016;Grillo, 2015;Tang & Lu, 2010). This metabolic pathway is responsible for the toxicity of ribociclib.…”
Section: Metabolic Profiles Of Ribociclibmentioning
confidence: 99%
“…For example, Walgren et al reported in 2005 that 5 out of 6 drugs withdrawn from the U.S. market since 1950 showed evidence for the formation of reactive metabolites. Reactive metabolite formation is, therefore, commonly considered an unwanted drug property . In drug discovery, bioactivation of drugs to reactive metabolites is evaluated in the early drug discovery stage to support the medicinal chemistry campaign in the attempt to design molecules with a low potential for bioactivation …”
Section: Introductionmentioning
confidence: 99%
“…Reactive metabolite formation is, therefore, commonly considered an unwanted drug property. 4,5 In drug discovery, bioactivation of drugs to reactive metabolites is evaluated in the early drug discovery stage to support the medicinal chemistry campaign in the attempt to design molecules with a low potential for bioactivation. [6][7][8][9][10][11] Reactive metabolites trapping is a widely applied assay in pharmaceutical industry to investigate the formation of reactive intermediates or metabolites in a biotransformation experiment.…”
Section: Introductionmentioning
confidence: 99%
“…A trapping agent can be co-incubated with the compound of interest in microsomal incubations, thus allowing it to react directly and form stable conjugates with any CYP-mediated reactive metabolites generated. These stable conjugates can then be detected by liquid chromatography-tandem mass spectrometry (LC-MS/MS) [ 5 , 10 ]. Recognizing the role of trapping agents in trapping reactive intermediates in close proximity to the CYP active site, it is possible that trapping agents also inhibit CYP activity, potentially modulating the CYP-mediated metabolism of the compound of interest and underestimating the formation of potential reactive metabolites.…”
Section: Introductionmentioning
confidence: 99%